2014
DOI: 10.1128/jvi.03312-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus Production by Aptamers against the Core Protein

Abstract: bHepatitis C virus (HCV) core protein is essential for virus assembly. HCV core protein was expressed and purified. Aptamers against core protein were raised through the selective evolution of ligands by the exponential enrichment approach. Detection of HCV infection by core aptamers and the antiviral activities of aptamers were characterized. The mechanism of their anti-HCV activity was determined. The data showed that selected aptamers against core specifically recognize the recombinant core protein but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
(36 reference statements)
1
29
0
Order By: Relevance
“…Afterwards, Shi et al developed a similar platform for early detection, coating the bottom of the well with C7, a DNA aptamer against HCV core labelled with biotin, and HCV-core antibody conjugated with horseradish peroxidase (HRP) is applied over the surface. The platform was applied to the detection of the protein in sera from HCV-infected patients and showed a proportional relationship between amplified RNA copies and HCV core protein concentration [82]. Moreover, Wang et al designed a rapid, easy-to-use diagnostic platform composed of lateral flow strips treated with thiol-DNA aptamers against HCV core antigen.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, Shi et al developed a similar platform for early detection, coating the bottom of the well with C7, a DNA aptamer against HCV core labelled with biotin, and HCV-core antibody conjugated with horseradish peroxidase (HRP) is applied over the surface. The platform was applied to the detection of the protein in sera from HCV-infected patients and showed a proportional relationship between amplified RNA copies and HCV core protein concentration [82]. Moreover, Wang et al designed a rapid, easy-to-use diagnostic platform composed of lateral flow strips treated with thiol-DNA aptamers against HCV core antigen.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…In the case of core, an essential protein for HCV viral assembly, Shi et al have applied for therapy the above-mentioned aptamers in diagnostics. In Huh7.5 cells, the aptamers against HCV core protein repressed viral production as a result of defective assembly of virus particle without stimulation of innate immune response [82]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…The high sensitivity was detected till 2.00 µg/ml of the coated antigen. Several mouse monoclonal antibodies targeting HCV core and envelope regions are already known and these antibodies are mainly used for antigen detection (Cagnon et al, 2004, Tabll et al, 2008and Shi et al, 2014.The monoclonal antibody (7G9) is targeted to the envelope glycoproteins E1 and E2.These envelope glycoproteins E1 and E2 are essential in the attachment and entry of the virus ( Sabo et al ,2011).E2 causes not only viral attachment to the cell membrane at its entrance but enhances also the neutralizing antibodies in the host. The envelope proteins play a major role in attachment and entry of virions into the body (Mazumdar et al, 2011) and (Park et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other research groups reported aptamers against HCV core (C) antigen for HCV detection. [109][110][111] Ghanbari et al immobilized an anti-C antigen aptamer onto graphene quantum dots (GOD), and the aptamer-GOD was placed on the surface of a glassy carbon electrode. 111 They demonstrated that the electrochemical aptamer-based biosensor effectively detects the HCV C antigen with the detection limit of 3.3 pg/mL.…”
Section: Hiv-1mentioning
confidence: 99%